On-Street and Off-Street Parking Analysis of Passenger Car in Malioboro, Yogyakarta - Mahmudah, Noor; Iswanto; Setiawan, Dian M.; Purwanto, Taufik H.; Nurkholis, Arif; Ramadhani, Sonia D. (Journal of Transportation Study Forum, 2024)
The increasing number of commercial activities in the Malioboro area, Yogyakarta will have an impact on the increasing traffic volume and parking space requirements. Therefore, this study aims to analyze the supply and demand of either on-street and off-street parking for passenger cars. To do so this study utilized quantitative method to evaluate the parking supply and demand. The analysis of parking supply considered the capacity for off-street parking at Malioboro Mall and on-street parking on Perwakilan Street, Yogyakarta. While parking demands are analyzed by considering Malioboro Mall floor area, number of visitors, and number of passenger cars parking at Malioboro Mall and Perwakilan street. The primary data was collected by conducting survey on-street and off-street parking of passenger cars, whereas secondary data was obtained from Transportation Office and Statistics Agency of Yogyakarta. The survey was conducted on the peak day (Saturday), at 10.00 AM to 20.00 PM by counting the passenger cars entering and exiting the parking areas. The result of analysis showed the maximum on-street parking accumulation (Ap) was 55 cars and off-street parking as many as 123 cars with parking volume (Vp) for on-street were 183 cars and off-street 421 cars. In addition, parking index (Ip) for on-street was 1.00 and off-street 1.171. Furthermore, the parking capacity (supply) consisted of on-street parking at Perwakilan Street was 55 cars and off-street parking at Malioboro Mall was 105 cars. The maximum on-street parking demand was 55 passenger cars, whereas off-street parking demand in Malioboro Mall were estimated by three conditions, where the first parking demand (Dmax1), the second (Dmax2) and the third one (Dmax3) were 160, 146, and 176 passenger cars respectively. Generally, it can be concluded that the parking demand exceeds the parking capacity (supply), so additional parking space for the passenger car is required.